Pengaruh Iklim Kerja dan Employee Engagement Terhadap Kinerja Pegawai pada Kantor Kementerian Agama Kabupaten Sikka - Rikardus Riki Supriyanto; Imanuel Wellem; Kristiana Reinaldis Aek (Universitas Nusa Nipa Maumere, 2026)
This study aims to: (1) describe Employee Performance, Work Climate, and Employee Engagement; and (2) analyze the influence of Work Climate and Employee Engagement on Employee Performance, both partially and simultaneously. The population of this study consisted of all employees of the Ministry of Religious Affairs Office of Sikka Regency, totaling 189 employees. Since the population size was relatively large, the sampling technique used was probability sampling with a simple random sampling method. The sample size was determined using the Slovin formula, resulting in 65 respondents. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, namely multiple linear regression analysis. Hypothesis testing was conducted using the F-test and t-test. The results of the descriptive analysis indicate that Employee Performance is categorized as good, Work Climate is categorized as good, and Employee Engagement is also categorized as good. The results of the t-test show that Work Climate has a positive and significant effect on Employee Performance. Furthermore, Employee Engagement also has a positive and significant effect on Employee Performance. The results of the F-test indicate that Work Climate and Employee Engagement simultaneously have a significant effect on Employee Performance. The coefficient of determination analysis shows that the two independent variables in this study are able to explain 47.9% of the variation in Employee Performance at the Ministry of Religious Affairs Office of Sikka Regency.